2011
DOI: 10.1242/jcs.087239
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of basement membrane movement: ECM patterning shapesHydrapolyps

Abstract: SummaryGrowth and morphogenesis during embryonic development, asexual reproduction and regeneration require extensive remodeling of the extracellular matrix (ECM). We used the simple metazoan Hydra to examine the fate of ECM during tissue morphogenesis and asexual budding. In growing Hydra, epithelial cells constantly move towards the extremities of the animal and into outgrowing buds. It is not known, whether these tissue movements involve epithelial migration relative to the underlying matrix or whether cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…Recent in vivo studies have shown that the ECM itself displays tissue-level movements that have been suggested to direct cell and tissue locomotion (Aufschnaiter et al, 2011;Benazeraf et al, 2010;Czirok et al, 2004;Filla et al, 2004;Zamir et al, 2006Zamir et al, , 2008. For example, during avian gastrulation the epiblast and the underlying sub-epiblastic ECM move together as a tissue composite (Zamir et al, 2008) and similar large-scale coordinated movements are observed among mesodermal cells and their surrounding ECM (Czirok et al, 2004;Zamir et al, 2006).…”
Section: Directed Cell Migration By Long-range Tissue Deformationmentioning
confidence: 99%
“…Recent in vivo studies have shown that the ECM itself displays tissue-level movements that have been suggested to direct cell and tissue locomotion (Aufschnaiter et al, 2011;Benazeraf et al, 2010;Czirok et al, 2004;Filla et al, 2004;Zamir et al, 2006Zamir et al, , 2008. For example, during avian gastrulation the epiblast and the underlying sub-epiblastic ECM move together as a tissue composite (Zamir et al, 2008) and similar large-scale coordinated movements are observed among mesodermal cells and their surrounding ECM (Czirok et al, 2004;Zamir et al, 2006).…”
Section: Directed Cell Migration By Long-range Tissue Deformationmentioning
confidence: 99%
“…Nonetheless, the evolutionary conservation of common ECM components and assembly processes across all extant eumetazoans (radiata and bilateria) (Fidler et al, 2014;Hynes, 2012) leaves tissue-scale motion in anamniotes (amphibia and fish) and invertebrates a distinct possibility. For example, in growing Hydra (an invertebrate with a relatively simple two cell-layered body plan), epithelial cells move towards the extremities and into the outgrowing buds, along with the associated primitive ECM (collagen 1 and laminin-rich mesoglea) via tissue-scale motion (Aufschnaiter et al, 2011). Thus, in the Hydra body column, the mesoglea is surprisingly dynamic, and is continuously displaced towards the ends of the animal (Fig.…”
Section: Tissue-scale Motion Patterns In Anamniotes and Invertebratesmentioning
confidence: 99%
“…Concerning the functions of the ECM, it was tested with multiple approaches (pharmacological, blocking antibodies, gene silencing via antisense RNA or insertion of exogenous ECM) in a variety of contexts, especially during reaggregation from dissociated tissues when the two epithelial cell layers come into contact in the absence of any ECM (Kishimoto et al, 1996;Murate et al, 1997), but also during regeneration and budding (Aufschnaiter et al, 2011). It turned out that the ECM plays an essential role for all these processes that are blocked when the ECM cannot form properly (see in Sarras, 2012).…”
Section: The Importance Of the Extra-cellular Matrix (Ecm) In Developmentioning
confidence: 99%